Oer, DEVELOPING HER VOICE: A Heroine’s Journey to Literary Individuation through Speculative Fiction - H ROSE (2023)
Abstract: Oer, Developing Her Voice: A Heroine's Journey to Literary Individuation through Speculative Fiction consists of original science fiction creative works set in postapocalyptic Wales alongside a personal case study integrated into a critical commentary. The research explores creative wholeness in the female psyche by utilising the Taliesin myth, childhood development, and alchemical and Jungian concepts. Thus, the reflective essay is part profoundly personal depth psychological case study and part memoir of a writer heroine's journey toward her voice and Awen, or writing flow, despite C-PTSD as a survivor of sexual abuse including Brownmiller’s ‘father rape’ (1993). The work proposes that creative expression post-childhood trauma directly relates to critical issues of attachment and childhood identity formation and that integration, individuation, and thus literary individuation may be cultivated. Tools explored include expressive arts, spiritual ritual, synchronicity, Sandplay therapy, dream, symbol work, and body-oriented process work, such as Bioenergetic, Primal Scream, and Reichian. Inner work addressed unconscious issues and traumatic cellular memory material; this facilitated the expulsion of poisonous animus or other psyche shadow introjects while cultivating psyche wholeness and a healthy animus or masculine 'soul-image', and thus literary individuation. The study highlights facilitating the development and voice of the Inner Child, akin to Jung's Divine Child. Grand and Alpert note the dearth of literature describing 'the psychic experience of incest' with its 'unspeakable, terrifying, disintegrative, and worldless realms' (1992); thus, the work may illuminate other disciplines. Finally, this academic narrative fulfils Charles L Whitfield's directive that healing the 'Child Within' entails 'sharing and telling our story' to reclaim the 'Real Self' and actualise 'transformation' (1987). Moreover, the research yields unique insights into researcher-screenwriter artistic practice, psychological development, and the processes of psyche and literary individuation, making a substantial contribution to screenwriting creative practice as research within the realms of creative writing and creativity research. Synopsis of Screenplay(s): A remote secret South Wales black ops military bioweapons research facility releases a Zai retrovirus as part of the US military collaborating with inhuman enemies crossing into planet Earth’s dimension and timeline to take over the world. Upon learning she and her little sister Rhan (11) were infected by their military scientist father Talan (50s), Abertha (14), who has lost all hope for a better future, steals a suicide drug. After Abertha refuses to help her sister fight back, the younger girl runs away into the dead zone. Then, Abertha reluctantly accepts the help of Daffyd (30s), a soldier seeking the truth about his suicide-victim brother Iwan, to escape the base. Mid horrific human-Zai hybrid mutation, Talan pursues, planning to fulfil his dark desires in the zone’s isolation. Mind-controlled soldiers and mutating hybrids in pursuit, Abertha and Daffyd trek through terrible earth changes where the alien world bleeds into and infects human reality and narrowly escapes or kills pursuers. Talan closes in, and Daffyd sacrifices himself so that Abertha has a chance to fight. After fighting and killing Talan, Abertha realises she saved Rhan and that she’ll never quit. She discards the suicide drug. Then Abertha learns that Rhan wasn't running away; she was running to. Like the Zai extraterrestrials, the youngest sister now sees multiple realities. In a secret lab, across the dead zone, is a Zai alien device that can reset time. Together, the girls reset reality and time to before the invasion.